PROGRAM PENGEMBANGAN BUDIDAYA PERIKANAN DI KECAMATAN BANTAN KABUPATEN BENGKALIS TAHUN 2015 - Puja Tusmara; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
An empowerment program that claims to be a program based on the wishes and needs of the community, but ironically the community still does not feel the ownership of the programs so it is not strange that many programs are only for the lifetime of the project and end up without a significant impact on people's lives as one of the programs of 16 programs of the Department of Marine Affairs and Fisheries Bengkalis is the development program of aquaculture. The problems in this research are; How is the implementation of fishery aquaculture development program in Kecamatan Bantan by Department of Marine and Fisheries of Bengkalis in 2015 ?. What are the obstacles in implementing the program of development of aquaculture in Kecamatan Bantan by the Department of Marine Affairs and Fisheries of in 2015? The type of research is qualitative research. Data collection techniques in research, interviews, Documentation Search, Observation. Sources of data in this study are primary data and secondary data. Based on the results of research conducted that the Program of freshwater fishery cultivation (pond) needs to evaluate the process of implementation of fishery aquaculture development program to determine the suitability between program planning and program implementation. Implementation of the program is in accordance with the planning prepared. But there are program planning that is not well realized, that is in the activity of fishery development and development. Inhibition of Fishery Cultivation Development Program is a communication between government agencies in empowering Fishery Development Program, the lack of human resources that can to implement the Program of Aquaculture Development in accordance with the existing policy, the subsequent lack of socialization which is mainly done by the fisheries and marine agencies. Keywords: Program, Development, Cultivation, Fisheries